STANDARD HETEROSIS FOR GRAIN YIELD AND OTHER AGRONOMIC CHARACTERS IN MAIZE (ZEA MAYS L.) UNDER NORMAL AND MOISTURE STRESS CONDITIONS - V. ULAGANATHAN; R. VINOTH; K. BAGHYALAKSHMI; SUVARNA RANI CHIMILI; A. GURUSAMY (The Bioscan, 2015)
Maize is one of the important food and forage crops with abundant natural diversity. The exploitation of heterosis is possible only when the parents involved in the crosses differ in their combining ability. Five inbred lines were crossed with each of three testers in a line × tester design to evaluate standard heterotic effects in maize during 2009-2010. For single plant yield 14 hybrids showed positive significant standard heterosis under normal condition values ranging from 17.68 (QPM-13 X S.C.B. 7853-1) to 77.39 % (QPM-14 X S.C.B. 7853-1) over the standard check variety Co 1. The hybrid QPM-18 X Co (BC) 1 showed positive significant standard heterosis under normal condition for single plant yield and other yield contributing characters. Twelve hybrids showed positive significant standard heterosis under moisture stress condition values ranging from 5.24 (QPM-13 X S.C.B. 7853-1) to 52.37 % (QPM-18 X S.C.B. 7853-1). Therefore, these aforesaid maize hybrids are the promising genotypes in future for evolution of superior maize hybrids for rainfed maize growing situations.